Stroke following Epidural Injections—Case Report and Review of Literature. Issue 1 (23rd June 2011) - Popescu, Alexandra; Lai, Daniel; Lu, Angela; Gardner, Kathy
<x xml:space="preserve">Abstract</x> ABSTRACT BACKGROUND AND PURPOSE To describe a growing number of cases associated with spinal cord and posterior circulation ischemia as a complication of cervical epidural steroid injection (CESI). METHODS Case report and review of literature. RESULTS Sixteen cases of spinal cord and posterior circulation ischemia were analyzed. Two cases had transient symptoms and 10 had long‐term sequelae. Four resulted in death. CONCLUSION Infarction is a rare but potentially devastating complication of CESI. It may occur despite the use of fluoroscopic guidance.